A microprocessor–based data acquisition and instrumentation system for the control of a rice–husk furnace. (4th August 2014) - Yaacob, Mashkuri; Ali, Baharuddin
The development of efficient combustion systems burning solid agricultural wastes for heat and power generation requires well designed microprocessor–controlled systems. This paper describes the development of a cost–effective system to control the stable and clean combustion of rice husks in a vertical cyclone furnace. Such a system is shown to be economically feasible.